1998
DOI: 10.1080/095400998116413
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Development of Modular Control Architectures for 1D Locomotion in Six-legged Animats

Abstract: An evolutionar y approach is used to design neural control architectures for virtual sixlegged anim ats. Using a geom etry-or iented variation of the cellular encoding scheme and syntactic constraints that reduce the size of the genetic search space, the developmental prog rams of straight locom otion controllers are ® rst evolved. One such controller is then included as the ® rst module in a larger architecture, in which a second neural module is evolved and develops connections to the ® rst one, so as to set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Results concerning the automatic production of 1-Dlocomotion controllers have been reported at length elsewhere [13]. In particular, it has been shown that some of the neural networks that have been obtained were capable of generating a tripod gait because they called upon four central pattern generators that were responsible for the rhythmic movements of the middle and back legs.…”
Section: A 2-d-locomotionmentioning
confidence: 94%
See 1 more Smart Citation
“…Results concerning the automatic production of 1-Dlocomotion controllers have been reported at length elsewhere [13]. In particular, it has been shown that some of the neural networks that have been obtained were capable of generating a tripod gait because they called upon four central pattern generators that were responsible for the rhythmic movements of the middle and back legs.…”
Section: A 2-d-locomotionmentioning
confidence: 94%
“…In [13], Manuscript we have implemented such a developmental process within the framework of an incremental evolutionary approach that made it possible to evolve one-dimensional (1-D) locomotion controllers in six-legged animats, i.e., in animats that walk along straight lines.…”
Section: Introductionmentioning
confidence: 99%
“…Their networks grow in a two-dimensional space using processes such as cell division and axon growth. Kodjabachian and Meyer also used connection growth mechanisms in their geometry-oriented version of CE called SGOCE [29]. Utilizing similar ideas of development, Miller evolved developmental programs that can construct the French flag (i.e.…”
Section: B Indirect Encodingsmentioning
confidence: 99%
“…We created three new developmental models initially inspired by Kodjabachian and Meyer's SGOCE paradigm [26][27][28][29][30] and NEAT [24,25,31]. By using them, we wanted to see how bilateral symmetry in neural networks could be generated and affect the behavior of a simulated robot.…”
Section: Our Approachmentioning
confidence: 99%